Loafing or Learning? The Demand for Informal Education - René Fahr (Institute for the Study of Labor (IZA), 2003)
Using detailed time use data for Germany a positive correlation is found between the level of schooling education and time investments in informal education. Two hypotheses explain this observation: (1) highly educated people have higher opportunity costs of their leisure time and thus prefer leisure activities which add to their market productivity (wage effect) and (2) highly educated people have a preference for ?high quality? leisure (taste effect). The demand for informal education is derived in a household production model accounting for both explanations. An empirical investigation finds evidence for both effects with the taste effect being the more important effect. Highly educated people accumulate human capital through their specific leisure time use. This increases the skill-gap between higher and lower educated people.
Keywords: J24; J22; D13; C24; 330; informal education; lifelong learning; time allocation; household production; censored LAD; Bildungsverhalten; Lebensverlauf; Hochqualifizierte Arbeitskräfte; Zeitallokation; Bildung; Nachfrage; Deutschland; Lebenslanges Lernen